ImAtHome: Making trigger-action programming easy and fun. (October 2017) - Fogli, Daniela; Peroni, Matteo; Stefini, Claudia
Highlights: A novel mobile application for smart home configuration and management is presented. A new interaction style for trigger-action programming is discussed. A user experiment is presented to compare the proposed application with Apple Home app. Abstract: ImAtHome is an iOS application for smart home configuration and management built over Apple HomeKit, a framework for communicating with and controlling home automation accessories. This paper describes the design and development of the visual interaction language made available in ImAtHome for empowering end users, without programming skills, to create event-condition-action rules that control home behavior. It can be regarded as an alternative approach to traditional trigger-action programming interfaces, where the user must define such rules by means of "if-then" constructs. Last but not least, attention has been put to make the interaction style as much coherent as possible with other iOS applications. The paper finally presents a user experiment, carried out with 30 participants according to a between-subject protocol, to evaluate the usability of ImAtHome and compare it with the official app for home automation recently released by Apple.